PENGARUH PENYULUHAN KESEHATAN TENTANG OBESITAS PADA REMAJA - Sri Kubillawati Kubillawati; Erny Elviany Sabaruddin; Nadila Aprianda (JURNAL KESEHATAN DAN KEBIDANAN, 2022)
Overweight and obesity have now become a serious global problem due to the rapidly increasing prevalence. Not only occurs in adults, many children and adolescents are obese. This study aims to determine the effect of health education on obesity in class XII adolescents at SMKN 58 East Jakarta. This type of research is quantitative with the Pre-Experimental method, the research design is one-group pre-test - post-test design. The research sample was 80 people using simple random sampling technique and using the McNemar test. The results showed that the students' knowledge before being given counseling (pre-test) was in the poor category (98.8%), after being given counseling (post-test) in the less category (37.5%). The results also showed the attitude of students before being given counseling (pre-test) in the negative category (52.5%) and after being given counseling (post-test) in the negative category (23.8%). So that there is an increase in knowledge and a significant change in respondents' attitudes after health education is carried out. Health education about obesity in adolescents affects the knowledge and attitudes of class XII students at SMKN 58 East Jakarta (p = 0.000). It is hoped that schools can play an active role in providing health education about nutrition, especially about obesity in adolescents by establishing cooperation between the health office or local health centers to monitor Body Mass Index and provide regular counseling by health workers.